Assessment of 222radon progeny loss in long tubing based on static filter measurements in the laboratory and in the field - Levin, Ingeborg; Schmithüsen, Dominik (Atmospheric measurement techniques, 2017)
Aerosol loss in air intake systems potentially hampers the application of one-filter systems for progeny-based atmospheric 222radon (222Rn) measurements. The artefacts are significant when air has to be collected via long sampling lines, e.g. from elevated heights at tall tower observatories. Here we present results from a study, determining 222Rn progeny loss from ambient air sampled via 8.2mm inner diameter (ID) Decabon tubing in the laboratory and from pre-installed 10mm ID tubing at the Cabauw meteorological tower in the Netherlands. Progeny loss increased steeply with length of the tubing, decreasing sampling efficiency to 66% for 8.2mm ID rolled-up tubing of 200m length at a flow rate of ca. 1m3h−1. Preliminary theoretical estimation of the loss yielded a sampling efficiency of 64% for the same tubing, when taking into account turbulent inertial deposition of aerosol to the walls as well as loss due to gravitational settling. At Cabauw tower, theoretical estimates of the loss in vertical tubing with 10mm ID and 200m lengths with flow rate of 1.1m3h−1 yielded a total efficiency of 73%, the same value as observed. 222Rn progeny loss increased strongly at activity concentrations below 1 Bqm−3. Based on our experiments, an empirical correction function for 222Rn progeny measurements when sampling through long Decabon tubing was developed, allowing correction of respective measurements for this particular experimental setting (tubing type and diameter, flow rate, aerosol size distribution) with an estimated uncertainty of 10-20% for activity concentrations between 1 and 2 Bqm−3 and less than 10% for activity concentrations above 2 Bqm−3.